Beehive Fireworks Festival Effect on the Nearby Atmospheric PM2.5 Level - Chih-Chung Lin; Jen-Hsiung Tsai; Yi-Chin Hsieh; Shui-Jen Chen (Aerosol and Air Quality Research)
Abstract Sudden short-term air pollution episode is now widely considered to harm human health. Previous research has found that firework activities rapidly raise the PM2.5 level in the ambient air. This study investigates the influence of Yanshuei Beehive Fireworks Festival on atmospheric PM2.5 from February 9th to 12th, 2017. The PM2.5 samples were gathered at 8 sampling sites around Yanshuei and Xinying before (background (B)), trial (T), during (D), and after (A) beehive firework display periods during the Yanshuei Beehive Fireworks Festival. The temporospatial differences of atmospheric PM2.5 before and after fireworks activities were explored. The atmospheric PM2.5 level in major activity areas was significantly higher from the background level in the trial and festival periods, and even after the activity. The study revealed that PM2.5 level reached the highest value of 327 µg m−3 at the major activity areas, which is 6.6 and 5.9 times those at upwind (49.8 µg m−3) and downwind (55.5 µg m−3) sites, respectively. Additionally, the T/B and D/B ratios were 3.01 and 7.19, respectively, around the major activity area. Conversely, the wind rose diagrams and contour lines of PM2.5 concentrations evaluated using Surfer 10.0 around the ambient air demonstrate that the atmospheric PM2.5 levels at Yanshuei and Xinying were similar to each other (35–45 µg m−3). However, the PM2.5 hardly diffused to distant places and accumulated in the local area around the boundary between Yanshuei and Xinying during the Beehive Fireworks Festival, since the wind speed was usually low or even stayed calm. The iso-concentration contour maps show that K+, Cl−, Mg2+, and NO3 − are related to firework release during the festival.